Otherness in Turkish-Greek relations: Continuity and change in the political discourse (1996-1999) - Ayanoğlu, Betül (My University, 2020)
In the social sciences, especially in the field of Political Science and International Relations, following the 1990s, multidisciplinary trends that have accelerated interdisciplinary scientific studies have begun to be seen frequently. These multifaceted systematic approaches have gradually influenced the disciplines in terms of providing depth and a wide range of analysis to scientific studies. Thus, like in the other disciplines, the framework of IR has also expanded and the principle of choosing only the state apparatus or state-based formations as the unit of study has been abandoned. In this process, Constructivism, which constitutes the basis of this study, made a groundbreaking contribution in terms of providing a middle way to theoretical debates; It has added a third dimension to the mainstream theories that evaluate identities as given and permanent and that do not find them worth concrete scientific studies due to their lack of providing explanations by the analysis of material elements, and to post-modern theories that confine identity studies within its boundaries. In this dissertation, the speeches given by the members of the ruling and opposition parties in the Turkish and Greek Parliaments were investigated comparatively with the method of interpretive discourse analysis. This study reveals the importance of intangible elements at least as much as the tangible elements, in Turkish-Greek relations, which play a crucial role in the perception, interpretation, and making decisions about political developments. Empirical findings based on the study of 3 different political developments (involving the state of war, conflict, and peace, respectively) that took place between the two countries within the years of 1996-1999 are as follows: Firstly, discourses are more effective than actions in the construction of national identity. Accordingly, discourses and narratives are decisive in the establishment and spread of social realities. Secondly, the self and other mutually and continually build each other, but it takes time to notice a continuity or change in the patterns of construction. Thirdly, nationalism and religion are influential in the strong marginalization used in the separation of peoples who have lived fused for centuries. Fourthly, two basic justifications are made so that othering can be adopted by all segments of society: Finding a legal basis and / or creating a historical background. As a result of employing interpretive discourse analysis, this study attempts to examine the main elements of self/other constructions, and whether there is a continuity or change in the identity approaches of the parties towards each other and the reasons for which the existing changes occurred are envisaged.

Sosyal bilimlerde, bilhassa Siyaset Bilimi ve Uluslararası İlişkiler alanında, 1990’lı yıllardan başlayarak, disiplinler arası bilimsel çalışmalara hız kazandıran multidisipliner eğilimler sıkça görülmeye başlanmıştır. Bu çok yönlü sistematik yaklaşımlar bilimsel çalışmalara derinlik ve geniş bir analiz sahası sunması bakımından bilim dallarını giderek etkisi altına almıştır. Böylece diğer bilim dallarında da olduğu gibi Uİ’nin de çerçevesi genişlemiş ve çalışma birimi olarak sadece devlet aygıtının veya devlet temelli oluşumların seçilmesi ilkesi terk edilmiştir. Bu süreçte bu çalışmanın da temel dayanağını teşkil eden İnşaacılık, kuramsal tartışmalara bir orta yol sunması bakımından çığır açıcı katkı sağlamıştır; kimlikleri verili ve değişmez olarak değerlendiren ve maddi unsurların analizi ile açıklanamamaları nedeniyle somut bilimsel çalışmaya uygun bulmayan ana akım teoriler ile kimlik çalışmalarını post-modern teorilerin sınırları içine hapseden yaklaşımlara üçüncü bir boyut kazandırmıştır. Bu doktora tezinde yorumsamacı söylem analizi metodu ile Türk ve Yunan Parlamentolarında iktidar ve muhalefet partilerinin üyeleri tarafından gerçekleştirilen konuşmalar karşılaştırmalı bir şekilde incelenmiştir. Çalışma, Türkiye-Yunanistan ilişkilerine en az somut unsurlar kadar etki eden soyut unsurların siyasi olayların algılanması, yorumlanması ve karara bağlanması açısından önemini ortaya koymaktadır. 1996-1999 yılları arasında iki ülke arasında vuku bulan 3 farklı siyasi gelişmenin (sırasıyla savaş, çatışma ve barış hallerinin) incelenmesine dayalı ampirik bulgular şu şekilde sıralanabilir: Birincisi, milli kimlik inşasında eylemlerden daha fazla söylemler etkili olmaktadır. Buna göre, sosyal gerçekliklerin tesisinde ve topluma yayılmasında söylemler ve anlatılar belirleyicidir. İkincisi, biz ve öteki, karşılıklı olarak, sürekli birbirlerini inşa ederler ancak bu inşanın süreklilik ve değişiklik gösteren dizgelerinin fark edilmesi zaman alır. Üçüncüsü, yüzyıllarca kaynaşık bir şekilde yaşamış halkların ayrıştırılmasında kullanılan güçlü ötekileştirmelerde milliyetçilik ve din etkilidir. Dördüncüsü, bir ötekileştirmenin toplumun bütün kesimleri tarafından benimsenebilmesi için iki temel gerekçelendirme yapılmaktadır: Hukuki dayanak bulmak ve/ya tarihsel arka plan oluşturmak. Bu çalışmada, yorumsamacı söylem analizi sonucunda biz/öteki inşasının temel unsurları ve tarafların birbirlerine yönelik kimliksel yaklaşımlarında bir devamlılık veya değişim olup olmadığı ve var olan değişimlerin hangi sebeplerle ortaya çıktığı ele alınmıştır.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: Milli kimlik oluşumu; Türk kimliği; Yunan kimliği; Türk-Yunan ilişkileri; Meclis konuşmaları; National identity formation; Turkish identity; Greek identity; Turkish-Greek relations; Parliamentary speeches